THE EVOLUTION AND IMPACT OF ISLAMIC ECONOMICS IN CONTEMPORARY FINANCIAL SYSTEMS IN INDONESIA - Naufaila Salsabila (Cahaya Ilmu Bangsa, 2024)
This paper investigates the implementation of Islamic economic principles in Indonesia and reviews the development and impact of Islamic Economics in the Contemporary Financial System in Indonesia. Indonesia, as a predominantly Muslim country, has great potential to develop a sharia based economy. In the face of various crises, including economic, moral, social, and cultural crises, Indonesia's economic growth must be balanced with the application of Islamic economic principles. These principles include the implementation of the concept of Tawhîd in economic activity, the principle of Khilâfa as human responsibility on earth, justice, equality, and productivity to achieve economic prosperity. The influence of Islamic Economics in the Contemporary Financial System in Indonesia is significant, with the rapid growth of Islamic financial institutions and various Islamic financial products. Nonetheless, there are challenges related to standardization, regulation, and supervision in the Islamic finance industry. Policy implications include improving Islamic financial literacy, developing Islamic economic infrastructure, and increasing Islamic financial product innovation. By implementing these policy implications, Indonesia can strengthen its position as a global Islamic economic center and improve economic welfare for the entire society.